Exploring public perspectives on synthetic biology and its integration with sex/gender characteristics - Heajin Kim; Chae-Won Lee; Eunmi Choi; Heisook Lee (Humanities & Social Sciences Communications)
Abstract Synthetic biology is a versatile technology with applications in the environment, medicine, food, energy, and services. Given its direct and indirect impacts on human health, the environment, and food development, sex/gender-integrated research is essential. However, this study is the first to systematically compare public perceptions of synthetic biology with and without sex/gender integration, addressing a critical gap in research. A survey of 300 Korean adults revealed that respondents, regardless of sex/gender, had some knowledge of synthetic biology and generally viewed it positively. Notably, respondents believed that incorporating sex/gender differences in synthetic biology would have a more positive impact than non-inclusive approaches, reinforcing the importance of inclusivity in biotechnology. These findings emphasize that integrating sex/gender into all aspects of synthetic biology development and industrialization is crucial for its sustainable advancement. The growing global emphasis on sex/gender-inclusive research suggests that synthetic biology, as a key future technology, must adopt inclusive approaches to enhance safety, reliability, and public trust.